2018
DOI: 10.1080/01658107.2018.1484932
|View full text |Cite
|
Sign up to set email alerts
|

Castleman Disease Presenting with Pseudotumour Cerebri and Myasthenia Gravis: A Case Report and Literature Review

Abstract: Castleman disease (CD) is a rare lymphoproliferative disorder that may present with various autoimmune, inflammatory, or neurologic syndromes. This is a case of a 21-year-old woman who presented with signs and symptoms of pseudotumour cerebri (PTC) who subsequently developed myasthenia gravis (MG), and was incidentally found to have a large mass in the posterior mediastinum. Upon resection, the mass was classified as unicentric CD involved with follicular dendritic cell sarcoma. Following treatment with IVIG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…To date, fewer than 15 published cases of concomitant CD and MG have been published with most cases representing localized hyaline vascular variant and only 3 reported multicentric. 3 A review of 14 published cases and the one presented here shows that patients have an average age of 35.2 ± 17.2 years. The cohort is 40% male.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…To date, fewer than 15 published cases of concomitant CD and MG have been published with most cases representing localized hyaline vascular variant and only 3 reported multicentric. 3 A review of 14 published cases and the one presented here shows that patients have an average age of 35.2 ± 17.2 years. The cohort is 40% male.…”
Section: Discussionmentioning
confidence: 74%
“…Castleman’s disease is a rare lymphoproliferative disorder first described in 1956. 2 It is characterized by angiolymphatic hyperplasia of the lymph nodes 3 and is classified by extent of the disease as either unicentric with single lymph node involvement or multicentric with systemic involvement. Unicentric disease is usually discovered incidentally on examination or imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with multicentric Castleman's disease tend to be older (50 to 70 years of age). Considerable interest is currently being focused on the role of human herpesvirus-8 in this lesion [6,7] and lies between element with the white blood cell -6 (IL-6) to increase related [8,9]. The multicentric form of the disease is quite virulent compared with the typically benign course of classic Castleman's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, up to 37.5% of these cases were associated with myasthenic crisis after surgical resection, an association much higher than the 5.4% incidence of myasthenic crisis following surgical resection of thymic epithelial tumors [8,9]. Table 1 includes the initial cases reported by Ishikawa et al, in addition to those reported after 2013 [3,[13][14][15][16][17][18]. One case of Castleman disease complicated by both myasthenia gravis and paraneoplastic pemphigus also included a myasthenic crisis; however, the crisis occurred during a hospitalization after a mucosal biopsy and not after the surgical resection of the mass [13].…”
mentioning
confidence: 99%